2005
DOI: 10.1186/1471-2334-5-54
|View full text |Cite
|
Sign up to set email alerts
|

Probable neuroimmunological link between Toxoplasma and cytomegalovirus infections and personality changes in the human host

Abstract: Background: Recently, a negative association between Toxoplasma-infection and novelty seeking was reported. The authors suggested that changes of personality trait were caused by manipulation activity of the parasite, aimed at increasing the probability of transmission of the parasite from an intermediate to a definitive host. They also suggested that low novelty seeking indicated an increased level of the neurotransmitter dopamine in the brain of infected subjects, a phenomenon already observed in experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 56 publications
1
50
0
4
Order By: Relevance
“…As rodents rely heavily on their olfactory abilities both for food acquisition and for predator avoidance (Dielenberg et al, 2001), altered neophilia/neophobia in the intermediate host may alter transmission probabilities of the parasite, either by increasing their chance of ingesting the parasite via foraging or through increasing their risk of predation by the definitive host. Humans are innately neophilic, and studies have suggested a negative correlation between novelty-seeking and latent toxoplasmosis in humans similar to that observed in rodents (Flegr et al, 2003;Novotná et al, 2005;Skallova et al, 2005). Novel odour assays in rodents may thereby be valuable for evolutionary and mechanistic studies into parasite altered innate behaviour.…”
Section: Relevance For T Gondii Researchmentioning
confidence: 99%
“…As rodents rely heavily on their olfactory abilities both for food acquisition and for predator avoidance (Dielenberg et al, 2001), altered neophilia/neophobia in the intermediate host may alter transmission probabilities of the parasite, either by increasing their chance of ingesting the parasite via foraging or through increasing their risk of predation by the definitive host. Humans are innately neophilic, and studies have suggested a negative correlation between novelty-seeking and latent toxoplasmosis in humans similar to that observed in rodents (Flegr et al, 2003;Novotná et al, 2005;Skallova et al, 2005). Novel odour assays in rodents may thereby be valuable for evolutionary and mechanistic studies into parasite altered innate behaviour.…”
Section: Relevance For T Gondii Researchmentioning
confidence: 99%
“…However, these negative associations were observed (especially in men) even when the health-related covariates were controlled. We suppose that a decrease of personality factor novelty seeking, which was observed in infected men and women in several studies (Flegr et al, 2003;Novotná et al, 2005;Skallová et al, 2005), could be responsible for the observed negative associations between toxoplasmosis and performing nonconventional sexual activities. This personality trait was measured, for example, by Cloninger's seven-factors Temperament and Character Inventory (TCI) questionnaire (Cloninger, Przybeck, Svrakic, & Wetzel, 1994) and is expected to negatively correlate with the concentration of dopamine in the ventral midbrain (Cloninger, Svrakic, & Przybeck, 1993).…”
Section: 36mentioning
confidence: 99%
“…Likewise, the potential interaction between T. gondii and coinfecting pathogen species may turn out to be important, particularly coinfection with other neurotropic agents such as cytomegalovirus. 28 Finally, it seems plausible that the genotypes of the T. gondii strains may play a role in the comparative impact of this parasite on host behavior between species and individuals. Toxoplasma gondii is composed of 3 major genotypes, Types I, II, and III (94% of all isolates), that have emerged as the dominant strains worldwide.…”
Section: Future Directionsmentioning
confidence: 99%
“…27 Moreover, it is plausible that the local immune response in the brain required to keep T. gondii dormant may alter cytokine levels that could then subsequently influence neuromodulator levels. 28 Neuromodulation may represent an ideal mechanism whereby T. gondii can influence, at least in part, the expression of host behavior. Studies investigating the neurological basis of anxiety, which often use the reaction of potential prey to cat stimuli as a model, have found that blocking the normally anxiogenic N-methyl-D-aspartic acid receptors in the amygdala, and/or provision of serotonin (5-HT) antagonists, causes rats to approach cat odors ''fearlessly, '' 29,30 in much the same way that T. gondii-infected rats do.…”
Section: Potential Mechanismsmentioning
confidence: 99%